2015
DOI: 10.1016/j.yexcr.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ loss activates ADAMTS-1-mediated EGF-dependent invasion in a model of esophageal cell invasion

Abstract: The TGFβ signaling pathway is essential to epithelial homeostasis and is often inhibited during progression of esophageal squamous cell carcinoma. Recently, an important role for TGFβ signaling has been described in the crosstalk between epithelial and stromal cells regulating squamous tumor cell invasion in mouse models of head-and-neck squamous cell carcinoma (HNSCC). Loss of TGFβ signaling, in either compartment, leads to HNSCC however, the mechanisms involved are not well understood. Using organotypic reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…In a similar study to ours, Le bras et al . established a 3D organotypic co-culture model using a collagen matrix, human esophageal epithelial cells, and human skin fibroblasts and demonstrated enhanced tumor proliferation and growth[43]. Concordant with our work, gene expression analysis revealed more than a 1.5 fold-increase in GPNMB compared to non-invasive cultures.…”
Section: Discussionsupporting
confidence: 85%
“…In a similar study to ours, Le bras et al . established a 3D organotypic co-culture model using a collagen matrix, human esophageal epithelial cells, and human skin fibroblasts and demonstrated enhanced tumor proliferation and growth[43]. Concordant with our work, gene expression analysis revealed more than a 1.5 fold-increase in GPNMB compared to non-invasive cultures.…”
Section: Discussionsupporting
confidence: 85%
“…80 On the other hand, ADAMTS-1 also facilitates cell invasion by cleaving heparin-binding epithelial growth factor–like growth factor and amphiregulin. 81,82 Interestingly, in our data from the protease arrays of the UMSCC1 cells, the secreted levels of ADAMTS-1 was identified as being significantly diminished in conditioned cell culture medium from UMSCC1 cells with increased miR-375 expression compared to its control line. The interactions of the theoretical miR-375 targets mentioned above with other invadopodia-associated proteins are shown in Supplemental Figure 1 (see supplemental digital content).…”
Section: Commentmentioning
confidence: 73%
“…TGFβ has been shown to stimulate collective migration primarily through extracellular-regulated kinase 1/2 (ERK1/2) activation [ 79 ]. On the other hand, using a three-dimensional organotypic culture system, we have described that inhibition of TGFβ signaling increases collection into the underlying extracellular matrix in a fibroblast- and MMP-dependent manner [ 80 ]. Additional research has demonstrated that tumor cell knockout of TGFβ signaling, through deletion of the type II receptor, drives fibroblast-stimulated collective migration and metastasis [ 81 ].…”
Section: Hijacked Developmental Processes and Their Contributions mentioning
confidence: 99%
“…However, it has been consistently shown that fibroblasts that lose responsiveness to TGFβ promote collective cell invasion [ 79 , 129 , 130 ]. These results suggest that, in contrast to activin A, TGFβ signaling in the tumor stroma is necessary to maintain an intact microenvironment and prevent tumor cell invasion, though it has been suggested that TGFβ may act through the reactive stroma, not the epithelial cell compartment, to promote tumor angiogenesis [ 2 , 4 , 6 , 80 , 134 ]. This is a significant point, where the functional consequences of TGFβ and activin A diverge.…”
Section: Contributions To Tumorigenesismentioning
confidence: 99%